UNCOVERING THE VEIL OF FORGETFULNESS IN LEARNING: Review In The Book Of Ta'lim Muta'allim - Fiyona, Putri; Hafidzi, Anwar (Muta'allim: Jurnal Pendidikan Agama Islam, 2024)
Forgetting, a reality that is often a scourge for knowledge seekers, becomes the main focus in the 12th chapter of Imam Al-Zarnuji's Ta'lim Muta'allim. This article delves into a deeper understanding of the causes of forgetting from the perspective of the classic book. The study identifies two main categories of causes of forgetting: internal and external factors. Internal factors include excessive busyness, anxiety, and sadness, as well as the consumption of certain foods. On the other hand, external factors include committing sins, seeing astonishing things, and passing through certain places. Furthermore, this article elaborates on the mechanisms behind each factor, explaining how they can interfere with the process of storing and retrieving information in memory. The discussion does not stop at identifying the causes, but offers practical solutions to overcome them. Through an in-depth analysis of Kitab Ta'lim Muta'allim, this journal makes a valuable contribution to understanding and overcoming forgetfulness, especially for students and knowledge seekers. This comprehensive understanding is expected to help them achieve success in gaining knowledge. Abstrak Lupa, realitas yang kerap kali menjadi momok bagi para penuntut ilmu, menjadi fokus utama dalam bab ke-12 Kitab Ta'lim Muta'allim karya Imam Al-Zarnuji. Artikel ini menyelami pemahaman mendalam mengenai penyebab lupa berdasarkan perspektif kitab klasik tersebut. Kajian ini mengidentifikasi dua kategori utama penyebab lupa: faktor internal dan eksternal. Faktor internal meliputi kesibukan, kegelisahan, dan kesedihan yang berlebihan, serta konsumsi makanan tertentu. Di sisi lain, faktor eksternal mencakup perbuatan dosa, melihat hal-hal yang mencengangkan, dan melewati tempat-tempat tertentu. Lebih lanjut, artikel ini menjabarkan mekanisme di balik masing-masing faktor, menjelaskan bagaimana hal-hal tersebut dapat mengganggu proses penyimpanan dan pengambilan informasi dalam memori. Pembahasan ini tidak berhenti pada identifikasi penyebab, tetapi menawarkan solusi praktis untuk mengatasinya. Melalui analisis mendalam Kitab Ta'lim Muta'allim, jurnal ini memberikan kontribusi berharga dalam memahami dan mengatasi lupa, khususnya bagi para pelajar dan penuntut ilmu. Pemahaman yang komprehensif ini diharapkan dapat membantu mereka dalam mencapai kesuksesan dalam menimba ilmu pengetahuan.